Carers' perceptions of the impact of home telehealth monitoring on the provision of care and sustainability of use. (25th November 2014) - Wade, Rachael; Cartwright, Colleen; Shaw, Kelly
<x xml:space="preserve">Abstract</x> Aims This paper aims to report carers' perceptions of the impact of home telehealth on the provision of care and the sustainability of home telehealth use. Method This paper is reporting on a sample of 15 carers who were involved in the telehealth arm of a larger controlled trial. Results Carers primarily believed that telehealth helped to provide better care. None of the carers had organised, or planned to organise, ongoing telehealth monitoring beyond the study. The main reason given for non‐sustained usage was the belief that the person they cared for no longer required, or would benefit from, the monitoring. Conclusion As the person being cared for was a frail older person with multiple chronic diseases and a history of recent hospitalisation, the non‐sustained usage of home telehealth by carers raises questions about what is needed to ensure sustainability of use; this requires further investigation.